Minimizing postharvest losses in pulses - Verma, Prasoon; Deo, Man Mohan (Indian Farming, 2024)
Pulses have always been in deficit to match the large domestic demand of vegetarian population of India. Combination diet of cereals and pulses on daily basis across the country makes pulses a staple food. After green revolution, the production of wheat and paddy increased several manifolds. But the similar growth could not be attained in case of pulses, where pulse production remainedstagnant for several decades. Pulses are mostly grown in rain-fed areas by resource poor small and marginal farmers. Unlike wheat and paddy, pulses are less responsive to inputs like nutrients and fertilizers. Concerted efforts were made through AICRPs on pulses involving NARS resulted into development of climate resilient and disease resistant improved varieties. Policy interventions suchas increased availability of quality seeds, enhanced minimum support prices, procurement for buffer stock, encouraged farmers to include pulses in crop cycle. Outcome of these interventions led to the all-time high production of pulses. But still there is need for import to meet inhouse requirements. It has also been observed that significant amount of pulses is lost in various postharvest handling and operations. Minimizing these losses will make more pulse proteins available for human consumption.